Monetary Policy, Structural Break, and the Monetary Transmission Mechanism in Thailand - Hesse, Heiko (World Bank, Washington, DC, 2012)
The paper studies monetary policy and the monetary transmission mechanism in Thailand in light of the Asian crisis in 1997. Existing studies that adopt structural vector auto-regression (VAR) approaches do not give a clear and agreed-upon view how monetary shocks are transmitted to the Thai economy that is subject to structural breaks. This study explicitly models a pre-crisis and post-crisis cointegrated VAR model. This analysis supports arguments that the trinity of open capital markets, pegged exchange rate regime, and monetary policy autonomy is inconsistent in the pre-crisis period. In contrast, the model points to an effective monetary policy in the post-crisis period. Further, the author analyzes the common driving trends of the model.